Mimesis and the Process of Becoming Human: Performativity, Repetition and Practical Knowledge. Issue 1 (April 2022) - Wulf, Christoph
Abstract : Although mimetic processes play an important role in the aesthetic experiences of art, literature, music, and theatre, they are also important in other areas. Mimetic processes are central to how human beings develop into humans. Plato and Aristotle were among the first to point this out. More recently, this ancient insight has been confirmed by research in evolutionary anthropology, neuroscience, and cultural anthropology. Cultural learning is essentially mimetic learning. It ensues through relationships with other people, as well as with nature, cultural objects, and artifacts. Hence, mimesis is of central importance for the development of cultural and practical knowledge. In this article, I argue that mimetic processes are processes of repetition and as such they are key elements both of memory and innovative action. They pave the way for innovations in post-literary cultures where a mimetic turn, or re -turn of attention to mimetic processes, is currently underway.